Degree Of Environmental Tax Contribution In Supporting Sustainable Development Dimensions. Analysis Study In Some Industrial Companies In Baghdad - Kaleel Esmael, Sahar (Opción, 2019)
The current study aimed to identify the degree of contribution of environmen- tal tax to achieving the dimensions of sustainable development by a group of industrial companies in Baghdad (General Company for Vegetable Oil Indus- try, Baghdad Soft Drinks Company, National Hydraulic Industries Company /Hydraulic Plant, Company General Construction Industries/Plastic Baghdad Plant) To identify the extent to which the study sample is aware of the con- cept of environmental tax in achieving sustainable development in order to reduce the depletion and conservation of natural resources, and to identify the extent of the study sample to understand the concept of environmental tax in achieving sustainable development in order to reduce the depletion and conservation of natural resources, and to achieve this was selected random sample of (62) of workers in industrial companies ,The questionnaire was used as a tool for collecting information, consisting of (25) paragraphs divided into four dimensions of the dimensionality of the study, The results of data analysis using SPSS V.23 showed that taxation contributes significantly to sustainable development., There are no statistically significant differences in the extent of awareness of the companies studied to the variables of type (sector, activity, waste) The degree to which environmental tax contributes to sustainable de- velopment and therefore does not affect the results of the study , The study presented a number of recommendations and research proposals.